Synthesis of Carboxymethyl Starch for increasing drilling mud quality in drilling oil and gas wells; IOP Conference Series: Earth and Environmental Science; Vol. 43 : Problems of Geology and Subsurface Development - Minaev K. M. Konstantin Madestovich; Martynova D. O.; Zakharov A. S. Aleksey Sergeevich; Sagitov R. R.; Ber A. A. Aleksandr Andreevich; Ulyanova O. S. Oksana Sergeevna (Latest Technologies in Oil and Gas Driling, 2016)
Title screen